Diplomasi Air Indonesia: Pelbagai Aspek dan Tujuan Negara - Gita Karisma; Iwan Sulistyo; Indra Jaya Wiranata (Andalas Journal of International Studies (AJIS), 2024)
Water diplomacy is needed to cooperate and find solutions to water issues. Water diplomacy can be political especially when it involves transnational waters and can even trigger conflicts between countries. Indonesia does not yet have transnational water and interstate water conflicts but remains actively involved in various world water forums. This research uses a qualitative approach with descriptive-analytical research to see Indonesia's water diplomacy. Access to clean water due to its vast territory has caused problems for Indonesia. This issue is one that Indonesia fights for in its water diplomacy. In addition, this research found that Indonesia's water diplomacy focuses on multilateralism. Indonesia is only at the starting point, but several aid projects for clean water and access have been obtained. Indonesia's water diplomacy involves political, integrative, and cooperative aspects. Politically, Indonesia is involved in various regional cooperation frameworks and has a partnership with the Mekong River Commission (MRC) even though Indonesia is not a Mekong River crossing country. Multilateral forums are also used to build cooperation and even fulfill integrative aspects such as efforts to create a Global Water Fund. In addition, Indonesia has shown leadership in engaging in several water policy issues while pushing its interests.